Inclusion of food and nutrition education in school curricula (Research, Society and Development, 2022)
This study aimed to investigate and analyze the needs and capacities of the public school system of Porto Alegre for the application of Law nº 13.666 / 2018. A descriptive cross-sectional design was used. A total of 114 elementary school teachers answered a qualitative questionnaire, through Web 2.0, composed of 14 closed questions. The main results were: i) most participants apply Food and Nutrition Education (EAN); ii) there is an association between the application of the EAN and the area of initial training, insufficient knowledge and the teacher's view of the relationship between the EAN and the subject taught; iii) low training in EAN; iv) the need for the management body to be involved; v) recognition of the EAN (91.2% answered that this is not a barrier). It is concluded that, despite the presence of barriers in the teaching area, a mark of disciplinary fragmentation, an emphasis was given to the role of the managing body in this process application of Law nº 13.666 / 2018.